Stress Induced Hyperglycemia in Early Childhood as a Clue for the Diagnosis of NEUROD1-MODY - Nur Berna Çelik; Naz Güleray Lafcı; Şenay Savaş-Erdeve; Semra Çetinkaya (Galenos Yayincilik, 2024)
Maturity-onset diabetes of young 'MODY' type 6 is a rare form of monogenic diabetes caused by mutations in neuronal differentiation 1 (NEUROD1). Clinical features vary in a large spectrum in terms of age and body mass index (BMI) at diagnosis. Here, we reported the youngest patient with a NEUROD1 variant to the best of our knowledge. A 2.1-year-old girl was referred to pediatric endocrinology clinic for elevated fasting BG (104 mg/dL) which was detected at another center where she had been evaluated for loss of appetite. Her maternal aunt and uncle had been diagnosed with type 2 diabetes mellitus (DM) at the age of 40 and 45 years; they were obese (BMI: 30.2 and 30.6 kg/m2). At the age of 3.7 years old, she was hospitalized for buccal cellulitis and plasma glucose concentration was 239 mg/dL at admission. Targeted next-generation sequencing (NGS) was performed considering the stress induced hyperglycemia without serious illness, negative islet cell antibodies and insulin autoantibodies, age at the presentation, and family history of DM. NGS analysis revealed a previously reported heterozygous missense variant in NEUROD1. Segregation studies showed that the identified variant was inherited from her 44-year-old mother with a BMI of 27.2 kg/m2 and a normal oral glucose tolerance test. Heterozygous NEUROD1 mutations cause low-penetrant diabetes that is heterogeneous in terms of clinical features as some patients fulfill the classic MODY definition and others are mimicking type 2 DM. Clinical manifestations and family history should be carefully evaluated in patients with stress induced hyperglycemia to identify candidate cases for molecular testing, and proper follow-up should be initiated in affected individuals.